Pokepodcast: producto transmedia sobre Pokémon - Solano Sanchez, Andres Martin (2023)
Pokepodcast is a transmedia production in Spanish, is related to the Pokémon franchise. Including sound and audiovisual content that complement each other for different platforms. There is a sound product named Pokepodcast, a podcast that has content about the anime, games, products and news of the same franchise, and an audiovisual product named Pokemaniacos, a program that includes content of product launches from the Pokémon franchise and anime news. Both programs are hosted by Pokémon connoisseurs and content creators, Pokedrew (Andrés Solano, Communicator and content creator specialized in Pokémon) and Rafiki (Jorge Herrera, Marketer and accomplished content creator related to Pokémon), in partnership with Shadow Games Peru, an official physical and virtual store of Pokémon products. The purpose of this project is to make the Pokémon universe known in Latin America, since there are no great references of the franchise in this part of the world.